Caracterização físico-química da água e mineralógica e geoquímica do material em suspensão e de sedimento de fundo do lago Amapá (Acre) - CARVALHO, Luis Carlos Farias de (Universidade Federal do Pará, 2019)
The Amazon area is characterized by its tropical rainforest and its great fluvial and lacustrine drainage basins. In the Southwest Amazonia, there are at least three great hydrographic basins (Juruá, Purus and Madeira rivers), where the oxbow lakes are very common. The Amapá Lake is on the right margin of Acre River - one of the principal tributaries of the Purus River -, close to the capital of the State of Acre, Rio Branco, as a typical oxbow lake that it was isolated from that river. Physical-chemical parameters measurements of the waters of Amapá Lake were accomplished during dry and rainy seasons in three stations to have an idea of the implications of the seasonal variation on the observed parameters. Samples were collected for elementary chemical analysis of the waters and suspended material, besides mineralogical analyses of the suspensate. Bottom sediments were collected in three survey holes, using a Livingstone-type manual probe, in a dry season, and they were submitted to chemical, mineralogical (XRD and SEM), grain size and geochronologic analyses. The waters of Amapá Lake present high turbid, STS, ammonia, (phosphate) and chloride values that indicate antropic action. The high concentrations of Na, Mg, K, Fe, Al, Mn, Ba and Sr are related to clay minerals (smectite and illite). The sediments of Amapá Lake are silt-clayey fine, distributed in beds (clear and dark), sometimes with organic particulate matter. The mineralogy of the sediments is homogeneous along the three holes and it is mainly represented by quartz, kaolinite, illite and smectite, besides albite and Kfeldspars. The vivianite occurs as pseudomorphs after organic matter debris. They are sediments with acid pH (4-5), unlike the waters, that are alkaline, and with low values of organic matter. The sediments are mainly composed by SiO2, Al2O3 and Fe2O3, besides K2O, MgO, TiO2, CaO, Na2O, P2O5 and MnO. That composition reflects abundance of quartz and clay minerals as illite and smectite. Iron contents are probably represented by amorphous sulphides or by clay minerals (smectite). The chemical results were compared with mean of the terrestrial upper crust and Post-Archean Australian Shales (PAAS). The sediments are impoverished in Na2O, CaO, MgO, K2O and SiO2 in small proportion, and enriched in MnO, TiO2, Fe2O3 and Al2O3. The values of Al2O3, Fe2O3, MnO and TiO2 are similar to the PAAS, being the sediments of the Amapá Lake comparable to those. They are immature sediments related to the clay minerals such illite and smectite and feldspars. Among the trace elements, As and Sb are more enriched in relation to the upper terrestrial crust. They are similar to PAAS. The sediments also resemble those shales via REE's being more enriched in Eu, Gd, Tb and Dy. The suspended sediment is compatible with the Acre River suspensate in mineralogy and chemical composition, partially diverging in the grain size. The Amapá Lake was formed on Early Holocene, at 3160 years BP, presenting average sedimentation rate of 1,1 mm/yr, in colmatation stage, still receiving load in suspension from Acre River, mainly when the inundations occur. The anthropic action centered in fish farmings, deforestations, disordered human expansion, besides an earth highway around the lake, contributes to its colmatation and eutrophication.